Pertanggungjawaban Hukum Pengelola Pondok Pesantren Al-Khoziny atas Kelalaian Konstruksi Bangunan - Sheva Dewa Ramadhani Boedihardjo; Subadi; Retno Catur Kusuma Dewi (Jurnal Hukum Lex Generalis, 2026)
This study examines the legal liability of the Al-Khoziny Islamic Boarding School management for construction negligence that led to the failure of the building structure and the victims. The study was conducted in a normative-analytical manner through a review of regulations, legal doctrine, construction literature, and technical reports. The results of the study indicate that the management can be asked for civil compensation under Article 1369 of the Civil Code, with reference to Law Number 28 of 2002 concerning Buildings which regulates technical standards and permits. The study recommends regular structural audits, the use of certified construction services, digitalization of permits, and an easy claims mechanism to ensure legal accountability and building safety in the Islamic boarding school environment.